2003
DOI: 10.1002/app.11684
|View full text |Cite
|
Sign up to set email alerts
|

Properties of n‐butyl methacrylate copolymer latex films derived from crosslinked latex particles

Abstract: Films obtained from copolymer latexes of n-butyl methacrylate (BMA) with a series of crosslinking monomers [i.e., a macromonomer crosslinker (Mac), ethylene glycol dimethacrylate (EGDMA), and aliphatic urethane acrylate] exhibited differences in their tensile properties and swelling behaviors. For P(BMA-co-EGDMA) copolymer, a dependence on the initiator type was obtained. It is postulated that the network microstructures for the various copolymers evolved as the result of the copolymerization reactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A series of papers by Ghazaly et al [21][22][23] provides further insight. These authors used miniemulsion polymerization to prepare NBMA copolymers with three crosslinkers, ethylene glycol dimethacrylate (EGDMA) and two polymeric di acrylates with M n of roughly 4000.…”
Section: Film Formation By ''Precoalescence'' Crosslinked Latexesmentioning
confidence: 95%
“…A series of papers by Ghazaly et al [21][22][23] provides further insight. These authors used miniemulsion polymerization to prepare NBMA copolymers with three crosslinkers, ethylene glycol dimethacrylate (EGDMA) and two polymeric di acrylates with M n of roughly 4000.…”
Section: Film Formation By ''Precoalescence'' Crosslinked Latexesmentioning
confidence: 95%
“…Th e emulsion technique was adopted by several scientists [56][57][58][59] to synthesize the crosslinked copolymers because, in emulsion polymerization, crosslinkers allow the control of particle morphology and enhance the mechanical properties of latexes used for paints and coatings. Th e kinetic and mechanistic features of emulsion polymerization are strongly refl ected in molecular weight and its distribution, chemical composition, and product properties.…”
Section: Polymerization Techniquesmentioning
confidence: 99%
“…To determine the diff erence in tensile properties and swelling behavior, a series of crosslinking monomers such as macromonomer crosslinker (Mac), EGDMA and aliphatic urethane acrylate were copolymerized with BMA by emulsion technique by El-Aasser et al [59]. Th ey found that copolymers prepared with Mac were tough in comparison with copolymers made with EGDMA.…”
Section: Crosslinking Monomer(s)mentioning
confidence: 99%
“…In order to determine the difference in tensile properties and swelling behaviour a series of cross-linking monomers such as macromonomer cross-linker (Mac), EGDMA and aliphatic urethane acrylate were co-polymerized with n-butyl methacrylate (BMA) by emulsion technique by El-Aasser and co-workers [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The coatings formulated with this emulsion have excellent damping properties and can be used for silencing and shock reducing of mechanical equipment, e.g., air conditioner. El-Aasser and co-workers [9] synthesized a latex film from the copolymer of BMA with a series of cross-linking monomers (i.e., a macromonomer cross-linker (MaC), EGDMA and aliphatic urethane acrylate) by mini-emulsion free-radical co-polymerization. Physical and chemical properties of films obtained form latexes prepared from the emulsion co-polymerization of BMA monomer with cross-linking monomers of different types and molecular weights.…”
Section: Cross-linkersmentioning
confidence: 99%